Empowering students’ critical thinking through the integration of statistical board teaching aids and problem-based learning - Amanda Adelia Safira; Puguh Darmawan (Polyhedron International Journal in Mathematics Education, 2025)
This study explores the impact of integrating a Statistics Board teaching aid within a Problem-Based Learning (PBL) model to foster students’ critical thinking skills in learning statistics, specifically in the topic of single data. Employing a qualitative case study approach, the research involved prospective mathematics teachers and undergraduate students enrolled in an Offering E class of a Mathematics Education Program. Data were obtained through classroom video recordings, observational notes from the lecturer, and the use of the Statistics Board during learning sessions. The collected data were analyzed using an interactive analysis technique, encompassing data condensation, data display, and conclusion drawing. Findings demonstrate that the incorporation of the Statistics Board within a PBL setting significantly enhances students' engagement and conceptual understanding while promoting the development of higher-order thinking, particularly critical thinking. The tangible and visual nature of the teaching aid enabled students to navigate abstract statistical concepts more intuitively and collaboratively solve contextual problems. This research affirms the pedagogical value of integrating concrete teaching aids and student-centered learning models in mathematics instruction. It recommends the use of the Statistics Board as an effective instructional resource for both practicing teachers and teacher candidates, offering a pathway toward more innovative, engaging, and cognitively enriching mathematics classrooms.